ChemInform Abstract: Bisacremines E—G, Three Polycyclic Dimeric Acremines Produced by Acremonium persicinum SC0105. Issue 7 (January 2016) - Wu, Ping; Xue, Jinghua; Yao, Lei; Xu, Liangxiong; Li, Hanxiang; Wei, Xiaoyi
Abstract: The isolation and structure elucidation of three novel acremines is reported.